2022
DOI: 10.1139/cjps-2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid application regulates vascular integrity and calcium allocation within apple fruits

Abstract: Calcium is a very poorly translocated nutrient in the flesh of apple fruits with the advancement of growth. Within the fruit, movement is further restricted towards distal portion relative to proximal. Even numerous foliar applications of calcium do not always achieve the desired effect. Thus, the objective of this study was to enhance the calcium allocation in distal parts of apple fruit in response to whole plant application of abscisic acid (ABA). Five-year-old apple plant of Super Chief Sandidge on M9 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The present study demonstrated that individual metabolites in papaya fruit exhibited unique accumulation patterns in different fruit parts during ripening. Although research on differences among tissue zones has been conducted on apples [ 13 , 19 , 24 , 25 ], there is limited information to determine the characteristics of each part of papaya fruit, with no comparative data in previous studies on papaya fruits. Doerflinger, Miller, Nock, and Watkins [ 13 ] compared the carbohydrate concentration of the stem-end, middle, and calyx-end in three apple cultivars (“Empire”, “Honeycrisp”, and “Gala”) during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that individual metabolites in papaya fruit exhibited unique accumulation patterns in different fruit parts during ripening. Although research on differences among tissue zones has been conducted on apples [ 13 , 19 , 24 , 25 ], there is limited information to determine the characteristics of each part of papaya fruit, with no comparative data in previous studies on papaya fruits. Doerflinger, Miller, Nock, and Watkins [ 13 ] compared the carbohydrate concentration of the stem-end, middle, and calyx-end in three apple cultivars (“Empire”, “Honeycrisp”, and “Gala”) during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, individual metabolites in papaya fruit showed various accumulation patterns in each fruit part during ripening. Research on the differences among different tissue zones has mainly been conducted on apples (Angmo et al ., 2022; Doerflinger et al, 2015; Lee et al ., 2019; Lewis, 1980). To the best of our knowledge, this is the first report to determine the characteristics of each part of the papaya fruit; there are no comparative data in previous studies on papaya fruits.…”
Section: Discussionmentioning
confidence: 99%
“…(2004) , xylem dysfunction begins earlier in the season for apple cultivars that are more susceptible to bitter pit. Other studies have also investigated the relationship between xylem vessel disruption and bitter pit in apples ( Amarante et al., 2012 ; Miqueloto et al., 2014 ; Angmo et al., 2022 ). According to Song et al.…”
Section: Xylem Vessel Disruptionmentioning
confidence: 99%